"Rapid actions of the neurosteroid allopregnanolone on ovarian and hypothalamic steroidogenesis: Central and peripheral modulation". (16th February 2020) - Cáceres, Antonella Rosario Ramona; Vega Orozco, Adriana Soledad; Cabrera, Ricardo Jorge; Laconi, Myriam Raquel
Abstract: The present study aimed to determine whether an i.c.v. administration of allopregnanolone (ALLO) rapidly modifies the hypothalamic and ovarian 3β‐hydroxysteroid dehydrogenase (3β‐HSD) enzymatic activity and gene expression in in vivo and ex vivo systems in pro‐oestrus (PE) and dioestrus I (DI) rats. Animals were injected with vehicle, ALLO, bicuculline or bicuculline plus ALLO and were then killed. In the in vivo experiment, the hypothalamus, ovaries and serum were extracted and analysed. In the ex vivo experiment, the superior mesenteric ganglion ‐ ovarian nerve plexus ‐ ovary system was extracted and incubated during 120 minutes at 37 ºC. The serum and ovarian compartment fluids were used to determine progesterone by radioimmunoanalysis. In the in vivo experiments, ALLO caused a decrease in hypothalamic and ovarian 3β‐HSD enzymatic activity during PE. During DI, ALLO increased hypothalamic and ovarian 3β‐HSD activity and gene expression. The ovarian 3β‐HSD activity increased in both stages in the ex vivo system; gene expression increased only during DI. ALLO induced an increase in serum progesterone only in D1 and in the ovarian incubation liquids in both stages. All findings were reversed by an injection of bicuculline before ALLO. Ovarian steroidogenic changes could be attributed to signals coming from ganglion neurones, which are affected by the acute central neurosteroid stimulation. The i.c.v. administration of ALLO via the GABAergic system altered 3β‐HSD activity and gene expression, modulating the neuroendocrine axis. The present study reveals the action that ALLO exerts on the GABAA receptor in both the central and peripheral nervous system and its relationship with hormonal variations. ALLO is involved in the "fine tuning" of neurosecretory functions as a potent modulator of reproductive processes in female rats.